Socio-ekonomski pomen gozdov v alpskem prostoru - Mavsar, Robert (Zbornik gozdarstva in lesarstva, 2005)
The importance of forests in the Alps is presented, both from the aspect of their owners and the society in general. While the owners strive primarily fordirect economic benefits from their forests, the societal importance has a wider range. Harmonising these expectations and thus enabling sustainable development of the Alpine area is a challenging but solvable task.
Keywords: Alpe; gospodarjenje z gozdovi; gozdovi; vloga gozdov